The Thinking Questions in English Textbooks for Students: A Content Analysis - Jemadi, Fransiskus; Ekalia, Yulian Juita; Neldis, Skolastika; Nadur, Mariani Mawasari (Makassar State University, 2025)
Abstract. The reading comprehension question level in textbook is crucial because it provides teachers with a base on what to use in the teaching learning process. This study is concerned with evaluating and contrasting the distribution of question levels in reading comprehensions in two EFL textbooks used in Indonesian secondary schools: English for Nusantara for grade VI (hereinafter referred to textbook 1) and When English Rings A Bell for grade VI (hereinafter referred to textbook 2). Both were published by the Ministry of Education and Culture of the Republic of Indonesia, although for different curriculums. This study focused on assessing Lower Order Thinking Skills (LOTS) and Higher Order Thinking Skills (HOTS) in reading passages using the revised Bloom's taxonomy. This study was designed using the descriptive qualitative approach and data was collected using a checklist table. The data were collected and evaluated to determine the percentages and frequencies associated with each level of thinking skills for the questions. The results showed that in both textbooks, LOTS were more prevalent than HOTS. In textbook 1, the percentage of LOTS is 79%, and in textbook 2, the percentage is 84%, whereas the percentage of HOTS is 21% in textbook 1 and 16% in textbook 2. Furthermore, memorizing (C1) is the most common question in both textbooks, accounting for 62% in textbook 1 and 78% in textbook 2. The findings highlight the need for curriculum developers and educators to reevaluate the complexity and cognitive demands of reading comprehension questions in English textbooks. By fostering higher-order thinking skills through more challenging and diverse questions, students can better prepare for real-world language use and critical analysis. As results, this study underlines the importance of aligning educational materials with the goals of developing students' critical thinking and problem-solving abilities, which are essential for their academic and future professional success.Keywords: Thinking questions, coursebook evalaution, reading questions